Palladium-Catalyzed Direct and Regioselective C-5 Desulfitative Arylation of Thiazolo[3,2-b]-1,2,4-triazoles with Sodium Sulfinates - Wang, Shaohua; Liu, Wenjie; Lin, Juan; Jiang, Yi; Zhang, Qi; Zhong, Yue (Synlett, 2014)
An efficient Pd(OAc)2-catalyzed direct arylation of thiazolo[3,2-b]-1,2,4-triazoles with sodium sulfinates has been developed. The reaction shows high regioselectivity, good reaction efficiency and excellent functional group compatibility. This approach provides a useful protocol for the preparation of functionalized thiazolo[3,2-b]-1,2,4-triazole derivatives.
Keywords: desulfitative arylation; C–H activation; thiazolo[3,2-b]-1,2,4-triazoles; sodium arylsulfinates